The Impact of Antibiotic Prophylaxis on a Retrospective Cohort of Hospitalized Patients with COVID-19 Treated with a Combination of Steroids and Tocilizumab - Francisco Javier Membrillo de Novales; Germán Ramírez-Olivencia; Maj. Tatiana Mata Forte; María Isabel Zamora Cintas; Maj. María Simón Sacristán; María Sánchez de Castro; Miriam Estébanez Muñoz (MDPI AG, 2023)
Objectives: In the context of COVID-19, patients with a severe or critical illness may be more susceptible to developing secondary bacterial infections. This study aims to investigate the relationship between the use of prophylactic antibiotic therapy and the occurrence of bacterial or fungal isolates following the administration of tocilizumab in hospitalized COVID-19 patients who had previously received steroids during the first and second waves of the pandemic in Spain. Methods: This retrospective observational study included 70 patients hospitalized with COVID-19 who received tocilizumab and steroids between January and December 2020. Data on demographics, comorbidities, laboratory tests, microbiologic results, treatment, and outcomes were collected from electronic health records. The patients were divided into two groups based on the use of antibiotic prophylaxis, and the incidence of bacterial and fungal colonizations/infections was analyzed. Results: Among the included patients, 45 patients received antibiotic prophylaxis. No significant clinical differences were observed between the patients based on prophylaxis use regarding the number of clinically diagnosed infections, ICU admissions, or mortality rates. However, the patients who received antibiotic prophylaxis showed a higher incidence of colonization by multidrug-resistant bacteria compared to that of the subgroup that did not receive prophylaxis. The most commonly isolated microorganisms were Candida albicans, Enterococcus faecalis, Staphylococcus aureus, and Staphylococcus epidermidis. Conclusions: In this cohort of hospitalized COVID-19 patients treated with tocilizumab and steroids, the use of antibiotic prophylaxis did not reduce the incidence of secondary bacterial infections. However, it was associated with an increased incidence of colonization by multidrug-resistant bacteria.